Investigating the Regulation of Adult Hippocampal Neurogenesis: Endogenous and Exogenous Cues - Pettit, Alexandra S. (Université d'Ottawa / University of Ottawa, 2012)
The discovery of stem and progenitor cells capable of ongoing neurogenesis in the adult mammalian brain has raised hope that we will one day be able to harness their intrinsic regenerative capacity following injury. Development of such therapeutic strategies relies on a comprehensive understanding of the underlying regulation of the neurogenic process. To this end, I show, in this thesis, that cultured post-natal hippocampal neural progenitor cells (NPCs) express a specific repertoire of connexins (Cx), a family of channel forming proteins critical for communication prior to the development of functional chemical synapses. I show that this pattern of Cx expression, specifically Cx43 and Cx45, is modulated by interaction with the extracellular matrix component laminin providing evidence of extracellular matrix-cell interaction in the regulation of intrinsic Cx expression and function in postnatal NPCs. In adult brain, I show, for the first time, that Cx45 localizes to all cell types of the neuronal lineage with the exception of the type 3 doublecortin (DCX)-positive NPCs. Using a loss of function approach, I show that this expression is required for the normal proliferation of type 1 nestin and glial fibrillary acidic protein-positive stem like NPCs but not for the differentiation or survival of their progeny in the adult hippocampus. With respect to exogenous pharmacological cues that influence hippocampal neurogenesis, this thesis also demonstrates that chronic treatment with a sub-set of selective serotonin reuptake inhibitor antidepressants, fluoxetine and escitalopram, increases the proliferation but not the survival of adult NPCs in healthy, non-depressed mice. Further, standard post-operative analgesia with the opiate buprenorphine inhibits the proliferation of DCX-positive adult NPCs and increases the survival of their progeny. Finally, over the course of the research for this thesis, it became clear that exposing research animals to even very subtle environmental changes can influence the basal neurogenic process. Ultimately this work further highlights the exquisite sensitivity of the regulation of what is already recognized to be a highly dynamic process and provides important insight into the neurogenic process that can be used to inform future therapeutic development and application.
Keywords: neurogenesis; depression; opiate; selective serotonin reuptake inhibitor; connexin; gap junction